A review of the U.S. workplace wellness market - Mattke, Soeren (Occasional paper, 2012)
This paper describes the current state of workplace wellness programs in the United States, including typical program components; assesses current uptake among U.S. employers; reviews the evidence for program impact; and evaluates the current use and the impact of incentives to promote employee engagement.